Teachers’ attitudes to the role of mobile education based on physical and health education in developing a healthy culture for primary school students during the COVID-19 pandemic - Aqel, Tagreed Numan; Abu Saada, Doaa Khalil (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to identify teachers’ attitudes to the role of mobile education based on physical and health education in developing a health culture for primary school students in light of the COVID-19 pandemic, and to explore the extent to which there are differences between the sample responses according to the variables (gender, grade, academic qualification, and years of age). Experience), the descriptive-analytical approach, and a questionnaire of (27) phrases were used as a tool for the study, which were distributed to a random sample of (65) male and female teachers for the first three grades and sports teachers for the basic stage. The results of the study showed that the arithmetic average of the estimates of the study sample on the domains of the questionnaire as a whole was (2.66 out of 3), which is a significant role, and at the level of domains: the field of infectious disease prevention got the highest average (2.81), then healthy nutrition with an average of (2.75), and thirdly The arts of sports activities with an average of (2.60), and finally, motor and sports skills with an average of (2.52), all of which estimate a significant role. The results also showed that there were no statistically significant differences between the average estimates of the study sample in all fields due to the variables (sex, grade, and years of experience). With the exception of the field of disease prevention and in favor of those with more than 11 years of experience, and there are statistically significant differences according to the qualification variable in the areas of healthy nutrition, motor skills and sports, and in favor of those with qualification (postgraduate studies), and based on the results, the two researchers recommended teachers to take advantage of mobile learning applications in the educational and educational scientific.